Keberadaan Bakteri Coliform dan Escherichia coli dalam Sumber Air Bersih Sebagai Penyebab Diare pada Rumah Tangga: Literature Review - Fathia, Nauriel; Utama, Winda Trijayanthi; Marcellia, Selvi; Carolia, Novita (CV. Jasa Sukses Abadi, 2025)
Water is an essential necessity for humans on Earth. Its role is crucial for daily activities, including household needs, industry, offices, and food production. In Indonesia, each person is estimated to require approximately 30–60 liters of water per day, whereas in developed countries, the demand per person ranges between 60–120 liters per day. The feasibility of water usage is regulated based on quality characteristics, referred to as water quality. One of the key indicators related to household water quality is biological parameters, particularly concerning the presence of coliform bacteria and Escherichia coli. These bacteria have a fecal-oral entry route, meaning that if consumed in excessive amounts, they can cause gastrointestinal diseases, primarily diarrhea. This study aims to examine the impact of coliform and Escherichia coli contamination in household water sources, leading to diarrhea cases. The research method used is a literature review and analysis. The findings indicate that the presence of Escherichia coli in household water sources, especially in areas with poor sanitation, poses a high health risk, particularly increasing the likelihood of diarrhea. Several factors contribute to this contamination, including the proximity of wells to pollution sources, inadequate waste management, and improper well construction that does not meet safety standards. These conditions suggest that environmental sanitation and the distance between water sources and potential contaminants play a significant role in water quality and public health. Through this study, it is expected that the community will be more aware of the importance of maintaining clean water used for household needs to prevent diarrhea-related diseases.